Performance Assessment of Mechanical Smoke and Heat Exhaust Ventilation Systems for Underground Car Parks with Natural Sources for Fresh Air Supply Using Computational Fluid Dynamics - Aşchilean Ioan; Rendeş Vicenţiu-Cătălin (Bulletin of the Polytechnic Institute of Jassy: Constructions, Architechture Section)
A particularly important role in the design of mechanical ventilation systems for the exhaust of smoke and heat from underground car parks is the sizing and location of sources for natural fresh air supply. Thus, the studies carried out were relevant to the fact that there are premises for an improvement of the functionality of these installations both from a technical and an economic point of view by sizing and arranging the gaps provided for the supply of fresh air, corroborated with the decision to use or non-use of impulse jet fans.